A bidirectional ups inverter utilising high frequency center-tapped transformer - Salam, Zainal; Ramli, Zulkifli (Penerbit UTM Press, 2004)
A new variation of transformer-isolated inverter for UPS application is proposed. It is basically similar to the circuit proposed by Koutroulis with the following modifications: 1) a modified modulation technique for the HF PWM inverter stage and 2) replacing the full bridge active rectifier with a center-tapped active rectifier. With these modifications, the switches count is reduced, and expectedly, the efficiency is increased. Furthermore, the modified PWM technique will ensure that the transformer can be utilised near to its full potential. This is due to the absence of the low frequency component that can result in transformer saturation. The paper will detail the design considerations for the proposed topology. It will primarily focus on the power circuit, modulation method, and the high frequency transformer design. To prove the concept, a 1-kW prototype inverter was built and tested.